Proceedings of the 20th Annual International Conference on Mobile Computing and Networking 2014
DOI: 10.1145/2639108.2639115
|View full text |Cite
|
Sign up to set email alerts
|

Discovering fine-grained RRC state dynamics and performance impacts in cellular networks

Abstract: To conserve power while ensuring good performance on resourceconstrained mobile devices, devices transition between different Radio Resource Control (RRC) states in response to network traffic and according to parameters specific to network operators. As RRC states significantly affect application power consumption and performance, it is important to understand how RRC state timers interact with network traffic patterns. In this paper, we show that the impact of RRC states on performance is significantly more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…In addition to the novel results we have found (discussed in more depth in our full-length paper [12]) this approach allows us to continue to maintain a database of cellular network performance worldwide that reflects the evolving cellular network. We have also contributed to the Mobilyzer project [11] aimed at developing a large, comprehensive dataset of network measurements worldwide from the client perspective.…”
Section: Discussion and Future Workmentioning
confidence: 93%
See 1 more Smart Citation
“…In addition to the novel results we have found (discussed in more depth in our full-length paper [12]) this approach allows us to continue to maintain a database of cellular network performance worldwide that reflects the evolving cellular network. We have also contributed to the Mobilyzer project [11] aimed at developing a large, comprehensive dataset of network measurements worldwide from the client perspective.…”
Section: Discussion and Future Workmentioning
confidence: 93%
“…In the full version of this paper [12], we investigate fine-grained RRC dynamics and performance in more depth, including through other measurement approaches. Prior work has focused on measuring RRC state configurations in a controlled setting or on specific device types which make RRC transition event logs directly available to applications [8,10,9,13].…”
Section: Introductionmentioning
confidence: 99%
“…We suspect that this is influenced by the RRC state machine at the radio layer as defined in the 3GPP standard [24], but we do not have visibility to actual RRC states using the commodity Nexus 4 phone to examine this further. Prior work (e.g., [19,34]) has also shown that inappropriately tuned RRC states impact web access performance. Overall, this suggests some potential misconfiguration or service differentiation at the radio layer for the MVNO B1 running over carrier B.…”
Section: Evaluation Of Page Load Timesmentioning
confidence: 99%
“…layer control plane messages used by the base station 1 to coordinate with the device. RRC state behavior has a significant impact on app performance and power consumption [22,33,40,41].…”
Section: Subjective and Objective Qoe Metricsmentioning
confidence: 99%